2014
DOI: 10.3402/gha.v7.23439
|View full text |Cite
|
Sign up to set email alerts
|

Public policy, health system, and community actions against illness as platforms for response to NCDs in Tanzania: a narrative review

Abstract: BackgroundMost low- and middle- income countries are facing a rise of the burden of non-communicable diseases (NCDs) alongside the persistent burden of infectious diseases. This narrative review aims to provide an inventory of how the existing policy environment, health system, and communities are addressing the NCDs situation in Tanzania and identify gaps for advancing the NCD research and policy agenda.MethodologyA literature search was performed on PubMed and Google scholar with full text retrieval from HIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…The prevalence of hypertension ranged from 12 to 69% among garage workers to rich traditional chiefs in West Africa ( 28 ). In Tanzania, NCDs were estimated at 27% ( 29 ). Uganda's NCD prevalence, although not very high, could be under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension ranged from 12 to 69% among garage workers to rich traditional chiefs in West Africa ( 28 ). In Tanzania, NCDs were estimated at 27% ( 29 ). Uganda's NCD prevalence, although not very high, could be under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Health systems in SSA must overcome multiple challenges to effectively manage the rising epidemic of hypertension and diabetes, including medication shortages, lack of diagnostic equipment, poor patient and physician knowledge and training, absent or inadequate treatment guidelines, cost of long-term treatment, and lack of effective screening programs, among others. [5][6][7][8][9][10][11] In Tanzania, for example, primary care provision is limited and in 2012 there were only 7.1 health care workers per 10,000 people, 12,13 an inadequate number to effectively manage and prevent NCDs. Furthermore, recent surveys of Tanzanian health care facilities have demonstrated that many lack basic functioning diagnostic equipment such as blood pressure cuffs or glucometers, and the majority of facilities lack protocols for NCD management.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, the Ministry of Health and Social Welfare promotes two important elements of FV intake, first is daily consumption and second is consumption in high quantities. Shortage of detailed evidence on FV consumption practices hampers targeted responses at policy and health system levels to promote FV consumption [ 32 ].…”
Section: Introductionmentioning
confidence: 99%